1997
DOI: 10.1074/jbc.272.24.15405
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Human Chorionic Gonadotropin α- and β-Subunit Promoters by AP-2

Abstract: Production of the placental hormone, chorionic gonadotropin (CG), increases dramatically as cytotrophoblasts fuse to form syncytiotrophoblasts. The CG ␣-and ␤-promoters are both responsive to cAMP, although the kinetics of cAMP stimulation are different. In an effort to understand the mechanisms of coordinate induction of these genes, AP-2 binding sites were identified in the promoter regions of the ␣ and CG␤ genes. AP-2 bound to the upstream regulatory element (؊186 to ؊156 base pairs (bp)) in the ␣-promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 45 publications
7
69
0
Order By: Relevance
“…As we demonstrated previously (11), the core element in C4 is similar to the TSE originally described in the ␣-hCG promoter that is recognized by putative TSEBP (12). The binding activity to TSE has been attributed to members of the AP2 family transcription factor (27), of which AP2␥ is the major AP-2 transcript in mouse placenta (34). TSE2, the second element we located in the placenta-specific enhancer of the aromatase gene, is not a known recognition sequence for transcription factors.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…As we demonstrated previously (11), the core element in C4 is similar to the TSE originally described in the ␣-hCG promoter that is recognized by putative TSEBP (12). The binding activity to TSE has been attributed to members of the AP2 family transcription factor (27), of which AP2␥ is the major AP-2 transcript in mouse placenta (34). TSE2, the second element we located in the placenta-specific enhancer of the aromatase gene, is not a known recognition sequence for transcription factors.…”
Section: Discussionsupporting
confidence: 63%
“…Recently, a binding protein to TSE in the ␣-hCG gene was identified as a transcription factor of the AP2 family (27). Binding activities to C2 and C4 were both competed by a consensus AP2 binding site.…”
Section: Resultsmentioning
confidence: 99%
“…Johnson et al (1997) also showed that AP2 and SP1 cooperate to induce gene activation, a finding confirmed in our overexpression experiments. It appears that the model postulated by Johnson et al (1997) and LiCalsi et al (2000) for the activation of human CGB expression in general also holds true for the marmoset, albeit with some differences. First is the enhancer function of the SP1 site (K805/K796), which had been postulated (Johnson et al 1997).…”
Section: Discussionsupporting
confidence: 85%
“…The presence of AP2 and SP1 binding sites within the placental core promoter correlates with previous human CGB studies that show the existence of two clusters of TFBS in the human CGB5 promoter (Bo & Boime 1992, Johnson et al 1997. Within these clusters, AP2 and SP1 were the most prominent factors (Steger et al 1993, LiCalsi et al 2000, Thackray et al 2010.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation